THE INFLUENCE OF TRUST, PRODUCT QUALITY AND PRICE PERCEPTION ON PURCHASE DECISIONS MEDIATED BY PURCHASE INTENTION - Aji Wardoyo, Sihat (Jurnal Locus Penelitian dan Pengabdian, 2023)
Indonesia has abundant natural resources, especially natural gas. However, using natural gas to meet household needs has yet to be utilized optimally, one of which is in Tarakan City. This research aims to determine the influence of trust, product quality and price perception through purchase intentions on purchasing decisions directly and indirectly. This research uses primary data with the data source distributing questionnaires via Google Forms. The data analysis technique uses Structural Equation Modeling (SEM) analysis, processed with SmartPLS version 3 software. The research results prove that the trust variable positively and significantly affects purchase intentions. The product quality variable has a positive and significant effect on purchase intentions. The price perception variable has a positive and significant effect on purchase intention. The purchase intention variable has a positive and significant effect on purchasing decisions. The trust variable does not affect purchasing decisions. The product quality variable does not affect purchasing decisions. The variable price perception through purchase intention does not affect purchasing decisions. From the results of the blindfolding analysis, results were obtained that showed good prediction accuracy with low criteria (0.02 – 015). The results of the model suitability analysis show that the suitability level for this research model is 63%.